(untitled) (Research Nepal Journal of Development Studies, 2019)
Tourism is simply selling air in the sky, but putting it in a beautiful balloon. Visit Nepal 2020 is a mega program of Nepal in tourism development. The event has to be a turning point of development of Nepalese tourism. It could be a milestone of Nepalese Tourism in economic transformation of the country. Vision 2020 of tourism ministry has set the vision of two million tourists arrival and one million job creation in Nepal. The vision and the target itself a massive challenge. Meeting the challenge is to create a favorable condition in economy. At this crucial time Nepal has to address the issues of opportunities and challenges. Objectively, to identify the opportunities and challenges of visit Nepal 2020 the study has been conducted. Methodologically the study is a descriptive qualitative analysis of different secondary information depending upon the reviews of different literature. In conclusion the study has revealed the opportunities as the arrival of two million tourists, creation of one million tourism related jobs, advancement of nature and culture, and adventure diversities, linkage with Indian and Chinese economies, development of Public-Private- Partnership models, disaster resilience chances, chances of major tourism development, decentralization of Nepalese tourism, and investment opportunities. Similarly, the challenges revealed by the study are insufficient infrastructures, inadequate investments, limited connectivity and weak national carriers, poor coordination among government agencies, scarcity of resources and marketing. To grab the opportunities Nepal governments, tourism ministries, departments, Nepal Tourism Board and entire tourism stakeholders have to meet the revealed challenges.